Tax Avoidance and Tax Risk Management Impacts on Earnings Response Coefficient - Masri, Indah (The International Journal of Business Review (The Jobs Review), 2020)
This research aims to analyse tax risk management role as a moderating variable in tax avoidance relationships with the earnings response coefficient. The research usesall samples of the non financial multinational companies on Indonesian and Malaysian stock exchanges. The outcome is tax risk management can strengthen the positive effect of tax avoidance on Earnings Response Coefficient. This proves that the tax risk management can be the control from the multinational corporations in handling tax avoidance. Companies that accomplish improved tax risk management can increase pre-tax income transparency that they present, thereby increasing earnings informativeness (ERC).